Pengolahan Limbah Minyak Jelantah menjadi Sabun Batang untuk Mencuci Pakaian sebagai Upaya Mengurangi Pencemaran Lingkungan - Monika, Aknes; Febrianto, Arip; Bekti, Agustin Setia; Makhrifat; Setyorini, Arifah Indah (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
Processing used cooking oil waste into bar soap for washing clothes as an effort to reduce environmental pollution is the aim of the student-entrepreneurship creativity program (PKM-K). The use of used cooking oil as a basic ingredient for bar soap for washing clothes which has economic value to provide innovative and creative ideas. The implementation methods used are lectures and discussions, practice and demonstrations, and evaluation. The results of this program become discussion material to find out program ideas. Next is practice and demonstration of selecting materials and providing a place as well as facilities and infrastructure to support the production process. Process (production), the process of making clothing bar soap. The output is a J-Clean product that is ready to be used and marketed to consumers. The last is evaluation, namely this stage is carried out when product production has been completed. The conclusion of the PKM-K program is processing used cooking oil waste into bar soap which is economically valuable and can create business opportunities for students.